Computers conduct utility performance. - Smith, Dennis (American City & County, 1999)
Systems and software can help cities prepare for competition. Municipal authorities are spending millions annually to maintain their information systems and management software. Better operations can help utilities save money and retain customers. Many medium-to-large municipal utilities are showing a readiness for deregulation and a willingness to compete in what is likely to be a volatile industry.